Image charge approximations of reaction fields in solvents with arbitrary ionic strength - Xu, Zhenli (2009)
In this paper, we report a new development of image charge approximations of reaction fields for a charge inside a dielectric spherical cavity immersed in an ionic solvent with arbitrary ionic strength. This new development removes the requirement of low ionic strength of the solvent in a previous result [S. Deng, W. Cai, Extending the fast multipole method for charges inside a dielectric sphere in an ionic solvent: high-order image approximations for reaction fields, J. Comput. Phys. 227 (2007) 1246–1266], thus extending the applicability of the image charge approximations of reaction fields in the modeling of bio-molecular solvation.